2002
DOI: 10.1071/wr00010
|View full text |Cite
|
Sign up to set email alerts
|

The diets of cats, foxes and dingoes in relation to prey availability in the Tanami Desert, Northern Territory

Abstract: In most areas of Australia, mammals constitute the staple diets of cats, foxes and dingoes. In central Australia the abundance of mammals is often too low to meet the dietary requirements of these carnivores and yet populations of cats, foxes and dingoes persist. To investigate alternative feeding strategies of cats, foxes and dingoes in arid environments, their diets were monitored in relation to prey availability in two areas of the Tanami Desert where rabbits do not occur. Dietary information was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 46 publications
10
124
2
Order By: Relevance
“…It is likely that efficient placental predators such as foxes and cats represent a greater predation risk to tammar wallabies than native predators such as quolls and snakes. Indeed, Macropus marsupials can constitute a substantial proportion of the diet of feral cats (Catling 1988;Paltridge et al 1997;Molsher et al 1999;Paltridge 2002) and the fox is the most likely predator of macropods on mainland Australia (Kaufmann 1974), and is considered the principal cause for the decline of tammar wallabies in Western Australia (Kinnear et al 1988). Although quolls and snakes presumably represent some degree of risk (Belcher 1995;Blumstein et al 2004;Glen and Dickman 2006), the wallabies may not perceive these predators as representing a great or immediate threat.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that efficient placental predators such as foxes and cats represent a greater predation risk to tammar wallabies than native predators such as quolls and snakes. Indeed, Macropus marsupials can constitute a substantial proportion of the diet of feral cats (Catling 1988;Paltridge et al 1997;Molsher et al 1999;Paltridge 2002) and the fox is the most likely predator of macropods on mainland Australia (Kaufmann 1974), and is considered the principal cause for the decline of tammar wallabies in Western Australia (Kinnear et al 1988). Although quolls and snakes presumably represent some degree of risk (Belcher 1995;Blumstein et al 2004;Glen and Dickman 2006), the wallabies may not perceive these predators as representing a great or immediate threat.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used the occurrence of fresh goanna tracks and pits that goannas create whilst foraging to index goanna abundance (Paltridge 2002;Bird et al 2014;Read and Scoleri 2014). Both indices have been validated against known abundances in other varanid species (Anson et al 2014).…”
Section: Goanna Activity Indicesmentioning
confidence: 99%
“…5a): (1) Cane toad activity should negatively affect goannas owing to lethal ingestion; (2) the foraging activity of goannas should negatively affect the abundance of skinks and dragons (Olsson et al 2005); (3) because of selective predation pressure, goanna activity should have a stronger impact on skinks than dragons (Sutherland 2011); (4) we used distance to the nearest dam as a proxy for the impact of cane toads because the impact of cane toads on goannas was negatively correlated with distance from dams (see ''Results'' section); (5) dingo activity should negatively affect goanna activity owing to predation (Paltridge 2002); (6) habitat modification resulting from grazing by livestock can have detrimental effects on both the abundance of goannas and of smaller lizard species such as skinks and dragons (James 2003); (7) time since fire was hypothesized to positively affect populations of goannas (Bird et al 2014) and to negatively affect skinks and dragons (Letnic et al 2004).…”
Section: Model Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this observation at the burrow-system, great desert skink still formed a relatively high proportion of dingo diet with 14% of dingo scats containing the remains of this species. Although an analysis of 12 000 dingo scats over a 20-year period found that, across most of Australia, medium-sized mammals are the preferred prey of dingoes (Corbett 1995), within arid environments reptiles have been found to be a dominant part of the dingo diet (Paltridge 2002;Newsome et al 2014). In support of this, we found that 62.5% of scats contained reptile remains (25% goanna, 21% skink exclusive of great desert skink; 10% dragon, 1.5% snake, 3% other reptile) compared with 15% of scats that contained the remains of mammals.…”
Section: Relative Predator Impact On Great Desert Skinkmentioning
confidence: 99%